Matoš i mazohizam - Jukić, Tatjana (Array, 2014)
Taking up Gilles Deleuze's presentation of masochism in Coldness and Cruelty and its critque of Freudian positions, my contribution focuses on a close reading of Antun Gustav Matoš’s “Pretzels, Fresh Pretzels”. It is the novella which works with many Deleuzian assemblages only to anticipate the positions underrepresented in Deleuze ; this is important not least where Matoš’s interest – like Deleuze’s – lies in an unpacking of the Austrian-Hungarian imaginary. I propose that such a reading be done against Viktor Tausk’s psychoanalytic studies of the Austrian- Hungarian army, as they provide the links seemingly missing between the languages and the narratives of Matoš, Freud and Deleuze.// U radu se fokusiram na Matoševu novelu “Pereci, friški pereci”, uz tezu da pomno čitanje Matoševe novele može poslužiti kao ishodište za analizu Deleuzeove rasprave o mazohizmu u studiji Hladno i okrutno, te za kritiku Freudova pristupa istome problemu. Riječ je o noveli u kojoj Matoš radi s mnogim konfiguracijama karakterističnima za Deleuzea, no pritom mapira pozicije koje kod Deleuzea ostaju nedomišljene ili po strani ; to je važno jer i Matoš i Deleuze teže ustvari razložiti strukturu austrougarskog imaginarija. Za takvo čitanje od posebnog su interesa psihoanalitičke studije Viktora Tauska s fokusom na austrougarsku vojsku, budući da se u njima naziru karike koje naoko nedostaju između jezikā i pripovijestī Matoša, Freuda i Deleuzea.